Contemporary Foreign Legal thought on the New Phenomena of Digital Transformation - I. R. Begishev; A. K. Zharova; E. A. Gromova; M. V. Zaloilo; I. A. Filipova; А. A. Shutova (Journal of Digital Technologies and Law)
.